2016
DOI: 10.1111/bcp.12834
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and pharmacodynamics of everolimus in patients with renal angiomyolipoma and tuberous sclerosis complex or lymphangioleiomyomatosis

Abstract: AIMSThe purpose was to determine the exposureÀresponse relationship of everolimus in patients with angiomyolipoma from the EXIST-2 trial and to analyze the correlation between exposure and plasma concentrations of angiogenic biomarkers in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 36 publications
(60 reference statements)
0
17
0
1
Order By: Relevance
“…Linear mixed models supported a statistically and clinically signifi cant association between a two-times increase in TN C min and a 28•3% reduction in seizure frequency. In the studies of subependymal giant-cell astrocytoma and angiomyolipoma, a two-times C min increase was associated with a non-clinically signifi cant 10% (unpublished) and 13% statistically signifi cant reduction in volumes, 30 respectively. This diff erence in exposure-response relationship might relate to higher interindividual variability of exposure and a threshold eff ect in the tumour-volume-based trials, or greater sensitivity of synaptic plasticity and neuronal hyperexcitability in this seizure study.…”
Section: Discussionmentioning
confidence: 94%
“…Linear mixed models supported a statistically and clinically signifi cant association between a two-times increase in TN C min and a 28•3% reduction in seizure frequency. In the studies of subependymal giant-cell astrocytoma and angiomyolipoma, a two-times C min increase was associated with a non-clinically signifi cant 10% (unpublished) and 13% statistically signifi cant reduction in volumes, 30 respectively. This diff erence in exposure-response relationship might relate to higher interindividual variability of exposure and a threshold eff ect in the tumour-volume-based trials, or greater sensitivity of synaptic plasticity and neuronal hyperexcitability in this seizure study.…”
Section: Discussionmentioning
confidence: 94%
“…Generell ist die Therapie bei TSC-assoziierten Symptomen eine lebenslange Therapie, da eine erneute Progression der Symptome nach Absetzen von Everolimus oder Sirolimus auftritt. In der Therapie der TSC-AML waren Talspiegel von Everolimus zwischen 3 und 8 ng/ml effektiv [66], möglicherweise sind auch niedrigere Talspiegel therapeutisch wirksam. Möglicherweise kann auch eine Dosisreduktion nach initialem Ansprechen sinnvoll sein [51,67].…”
Section: Sicherheit Einer Mtor-inhibitor-therapieunclassified
“…The eligibilities were carefully assessed in 11 full-text articles. Finally, only 9 studies met the inclusion criteria for the systematic review, including 2 RCTs [ 14 , 20 , 21 ], 6 single-arm trials [ 12 , 17 , 22 – 25 ], of which 7 studies were used for the meta-analysis. Notably, Budde et al [ 21 ] reported the accurate data on the serum VEGF-D levels, which were not elaborated in the initial study [ 20 ], so we cited the two separate studies as the same RCT.…”
Section: Resultsmentioning
confidence: 99%